Homogenisation Problems for Free Discontinuity Functionals with Bounded Cohesive Surface Terms - Dal Maso, Gianni; Toader, Rodica (Archive for rational mechanics and analysis, 2024)
We study stochastic homogenisation problems for free discontinuity functionals under a new assumption on the surface terms, motivated by cohesive fracture models. The results are obtained using a characterization of the limit functional by means of the asymptotic behaviour of suitable minimisation problems on cubes with very simple boundary conditions. An important role is played by the subadditive ergodic theorem.